Razumevanje javnega sektorja in slovenska gospodarska politika po letu 2008 - Tajnikar, Maks (Teorija in praksa, 2015)
The authors of this paper first discuss the correct understanding of the role and place of the public sector in any economy, and then analyse how misconceptions about the public sector have affected Slovenian economic policy following the onset of the crisis in 2008. The authors argue that the maximisation of social efficiency and overall well-being of a society determines whether a specific economic sector is included in society's public sector. The size of the country's public sector relative to the size or share of the private sector is in turn determined by the structure of aggregate demand. Based on their discussion about the role of the public sector, the authors highlight errors made in shaping the economic policy adopted in Slovenia to combat the economic crisis since 2008.
Keywords: economic policy; economics; ekonomija; ekonomska politika; javni sektor; public sector; Slovenia; Slovenija